Computational and functional prioritization identifies genes that rescue behavior and reduce tau protein in fly and human cell models of Alzheimer disease. - Stephens, M.C.; Li, J.; Mair, M.; Moore, J.; Zhu, K.; Tarkunde, A.; Amoh, B.; Perez, A.M.; Bhakare, A.; Guo, F.; Shulman, J.M.; Al-Ramahi, I.; et al. (American Journal of Human Genetics, 2025)
Genome-wide association studies (GWASs) in Alzheimer disease (AD) have uncovered over 70 loci significantly associated with AD risk, but identifying the true causal gene(s) at these loci requires systematic functional validation that is rarely performed due to limitations of time and cost. Here, we integrate transcriptome-wide association study (TWAS) with colocalization analysis, fine-mapping, and additional annotation of AD GWAS variants to identify 123 genes at known and suggestive AD risk loci. A comparison with human AD brain transcriptome data confirmed that many of these candidate genes are dysregulated in human AD and correlate with neuropathology. We then tested all available orthologs in two well-established Drosophila AD models that express either wild-type tau or secreted ?-amyloid (?42). Experimental perturbation of the 60 available candidates pinpointed 46 that modulated neuronal dysfunction in one or both fly models. The effects of 18 of these genes were concordant with the TWAS prediction, such that the direction of misexpression predicted to increase AD risk in humans exacerbated behavioral impairments in the AD fly models. Reversing the aberrant down- or upregulation of 11 of these genes (MTCH2, ELL, TAP2, HDC, DMWD, MYCL, SLC4A9, ABCA7, CSTF1, PTK2B, and CD2AP) proved neuroprotective in vivo. We further studied MTCH2 and found that it regulates steady-state tau protein levels in the Drosophila brain and reduces tau accumulation in human neural progenitor cells. This systematic, integrative approach effectively prioritizes genes at GWAS loci and reveals promising AD-relevant candidates for further investigation as risk factors or targets for therapeutic intervention.